1992
DOI: 10.1016/0965-1748(92)90113-s
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical studies of amylases in the silkworm, Bombyx mori L.: Comparative analysis in diapausing and nondiapausing strains

Abstract: Abstract--Different amylase enzymes were identified by analysis of digestive fluid and haemolymph in diapausing and nondiapausing strains of silkworm, Bombyx mori. The diapausing strain showed negligible digestive amylase activity at a pH range of 3-11, while the nondiapausing strain registered strikingly higher amylase activity at pH 9.2. Higher levels of undigested starch was found in the faecal matter of the diapausing strain, which is consistent with the negligible digestive amylase activity. Developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
22
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 17 publications
3
22
0
1
Order By: Relevance
“…In a similar kind of study, maximum amylase activity was found in late middle part of the fifth instar of silkworm 16 . Higher digestive amylase activity in low yielding breeds (multivoltines) and low digestive amylase activity in high yielding breeds (bivoltines) exhibited in the present study also receive support from the findings of many other authors who revealed that diapausing strains showed negligible digestive amylase activity, while the non-diapausing strains registered strikingly higher amylase activity 4,14,17 . However variations in the levels of digestive amylase activity could be attributed to the physiological status of the insect that increases its feed consumption and utilization efficiencies.…”
supporting
confidence: 80%
See 4 more Smart Citations
“…In a similar kind of study, maximum amylase activity was found in late middle part of the fifth instar of silkworm 16 . Higher digestive amylase activity in low yielding breeds (multivoltines) and low digestive amylase activity in high yielding breeds (bivoltines) exhibited in the present study also receive support from the findings of many other authors who revealed that diapausing strains showed negligible digestive amylase activity, while the non-diapausing strains registered strikingly higher amylase activity 4,14,17 . However variations in the levels of digestive amylase activity could be attributed to the physiological status of the insect that increases its feed consumption and utilization efficiencies.…”
supporting
confidence: 80%
“…Digestive juice samples were centrifuged @ 10,000 r/10 min (ref. 4). The supernatant was transferred to new tubes and kept at -20C for analysis.…”
mentioning
confidence: 99%
See 3 more Smart Citations